Vascular endothelial growth factor: Potential predictor of treatment response in major depression. (17th November 2017) - Clark-Raymond, Anne; Meresh, Edwin; Hoppensteadt, Debra; Fareed, Jawed; Sinacore, James; Garlenski, Brittany; Halaris, Angelos
Abstract: Objectives : The aim of the study was to evaluate baseline plasma VEGF levels as a potential predictor of response to antidepressant pharmacotherapy. The study also sought to determine whether baseline plasma VEGF would be useful in predicting treatment outcome when two pharmacodynamically diverse agents with established antidepressant efficacy, escitalopram and quetiapine, were administered monotherapeutically to MDD patients.Methods : Two groups of qualifying MDD subjects were enrolled. One group was treated with escitalopram and the other with quetiapine. Plasma concentrations of VEGF were measured using Randox Technologies at baseline, and at weeks 8 and 12 of treatment.Results : We stratified the MDD patients into those who remitted and those who failed to respond. Mean baseline VEGF for the remitters and non-responders was 9.61  and 5.40 pg/ml, respectively ( P  < 0.0005). Using optimal data analysis a cut score of 7.49 pg/ml for baseline plasma VEGF distinguished remitters from non-responders with a 63% overall accuracy. The remission rate was comparable for both drugs (73 and 81% for quetiapine and escitalopram, respectively). VEGF levels did not significantly change following antidepressant treatment with either escitalopram or quetiapine when measured at 8 and 12 weeks; this result held true for both remitters and non-responders.Conclusions : Our results suggest that VEGF may predict response to antidepressant treatment and may ultimately prove to be a potential biomarker that can be measured with a routine blood draw at the point of service.